RUTBC2 protein, a Rab9A effector and GTPase-activating protein for Rab36. - Nottingham, R; Pusapati, G; Ganley, I; Barr, F; Lambright, D; Pfeffer, SR (2012)
Rab GTPases regulate vesicle budding, motility, docking, and fusion. In cells, their cycling between active, GTP-bound states and inactive, GDP-bound states is regulated by the action of opposing enzymes called guanine nucleotide exchange factors and GTPase-activating proteins (GAPs). The substrates for most RabGAPs are unknown, and the potential for cross-talk between different membrane trafficking pathways remains uncharted territory. Rab9A and its effectors regulate recycling of mannose 6-phosphate receptors from late endosomes to the trans Golgi network. We show here that RUTBC2 is a TBC domain-containing protein that binds to Rab9A specifically both in vitro and in cultured cells but is not a GAP for Rab9A. Biochemical screening of Rab protein substrates for RUTBC2 revealed highest GAP activity toward Rab34 and Rab36. In cells, membrane-associated RUTBC2 co-localizes with Rab36, and expression of wild type RUTBC2, but not the catalytically inactive, RUTBC2 R829A mutant, decreases the amount of membrane-associated Rab36 protein. These data show that RUTBC2 can act as a Rab36 GAP in cells and suggest that RUTBC2 links Rab9A function to Rab36 function in the endosomal system.